Simpul-Simpul Strategis Pengembangan Asuransi Pertanian untuk Usahatani Padi di Indonesia - nFN Sumaryanto; Ahmad Rozany Nurmanaf (Forum penelitian Agro Ekonomi, 2007)
EnglishIn line with climate change, it is predicted that risk and uncertainty of rice farming will be swelling up.  To cope with its negative effects, conventional approach using one or combination of strategy of production, marketing, financial, and informal credit might not be appropriate. Development of agricultural insurance specifically rice farming, is highly considered. This article is aimed at a review of some strategic aspects for developing the agricultural insurance, especially related to the basic prerequisites for designing the scheme. To get better understanding, its perspective with empirical condition of rice farming in Indonesia is enriched with lesson learned from other countries that here previously developed the agricultural insurance.IndonesianSeiring terjadinya perubahan iklim, diperkirakan risiko dan ketidakpastian dalam usahatani padi meningkat. Untuk mengatasi hal itu pendekatan konvensional melalui penerapan satu atau kombinasi strategi produksi, pemasaran, finansial, ataupun memanfaatkan kredit informal dikhawatirkan tidak memadai. Sistem proteksi melalui pengembangan asuransi pertanian sangat layak dipertimbangkan. Tinjauan ini ditujukan untuk membahas simpul-simpul strategis yang harus dicermati dalam pengembangan asuransi pertanian untuk usahatani padi. Bahasan difokuskan pada pilar-pilar pokok perancangan skim asuransi pertanian. Untuk memperoleh pemahaman yang lebih baik, perspektifnya dengan kondisi empiris usahatani padi di Indonesia diperkaya dengan pengalaman dari negara-negara lain yang telah mengembangkan asuransi pertanian.